Exploring the intention to consume organic food among generation-Y research management institute / Juan Rizal Sa'ari and Koe Wei Loon - Sa'ari, Juan Rizal; Koe, Wei Loon (Research Management Institute (RMI), 2012)
Food is a basic necessity for the survival of humankind and people consume various types of food every day. Nowadays, with the demand for high quality of life, organic food has started to gain the consumers' attention in the food market. Evidence from Europe and North American regions has proven that organic food demand has soared overwhelmingly. There is no doubt that organic food can help people to lead a healthy life and it has a great potential to prosper in the region. However, research into the organic food market in Malaysia is still very lacking, especially among the young consumers such as Generation-Y because it is considered new in Malaysia. As such, this study was carried out to determine the level of intention to consume organic food and to verify the relationship between influencing factors and intention to consume organic food among Generation-Y. The respondents were selected from undergraduate students of a local university. Based on the descriptive statistics, the study found that most respondents have the average intention to agree in consuming organic food. The inferential statistical tests showed that environmental concern and food safety play a significant and positive effect on influencing intention to consume organic food among Generation-Y. However, other factors such as perceived cost, perceived quality, health consciousness, trust and social value are deemed as less significant in predicting intention to consume organic food among Generation-Y. Recommendations for organic food producers, consumers, policy makers and future researchers have also been put forth at the end of this study.